(untitled) (Eurasian Journal of Ecology, 2016)
Osmotic rezisiz of membranes of red corpuscles and activity of katalaz was determined for pregnant and laktation rats at influence of acoustic stress.On results research at exposed to acoustic stress of pregnant and laktation rats osmotic rezizis and activity of katalaz of membranes of red corpuscles as compared to a control group appeared below